Prevalence and determinants of hypertension among urban slum dwellers in Bangladesh - Sabuj Kanti Mistry; Md. Belal Hossain; Mahmood Parvez; Rajat Das Gupta; Amit Arora (BMC, 2022)
Abstract Background In low- and middle- income countries such as Bangladesh, urban slum dwellers are particualry vulnerable to hypertension due to inadequate facilities for screening and management, as well as inadequate health literacy among them. However, there is scarcity of evidence on hypertension among the urban slum dwellers in Bangladesh. The present study aimed to determine the prevalence and factors associated with hypertension among urban slum dwellers in Bangladesh. Methods Data were collected as part of a large-scale cross-sectional survey conducted by Building Resources Across Communities (BRAC) between October 2015 and January 2016. The present analysis was performed among 1155 urban slum dwellers aged 35 years or above. A structured questionnaire was adminstered to collect data electronically and blood pressure measurements were taken using standardised procedures. Binary logistic regression with generalized estimating equation modelling was performed to estimate the factors associated with hypertension. Results The prevalence of hypertension was 28.3% among urban slum dwellers aged 35 years and above. In adjusted analysis, urban slum dwellers aged 45-54 years (AOR: 1.64, 95% CI: 1.17-2.28), 55-64 years (AOR: 2.47, 95% CI: 1.73-3.53) and ≥ 65 years (AOR: 2.34, 95% CI: 1.47-3.72), from wealthier households (AOR: 1.94, 95% CI: 1.18-3.20), sleeping < 7 h per day (AOR: 1.87, 95% CI: 1.39-2.51), who were overweight (AOR: 1.53, 95% CI: 1.09-2.14) or obese (AOR: 2.34, 95% CI: 1.71-3.20), and having self-reported diabetes (AOR: 3.08, 95% CI: 1.88-5.04) had an increased risk of hypertension. Moreover, 51.0% of the participants were taking anti-hypertensive medications and 26.4% of them had their hypertension in control. Conclusions The findings highlight a high burden of hypertension and poor management of it among the slum dwellers in Bangladesh requiring a novel approach to improve care. It is integral to effectively implement the available national non-communicable disease (NCD) control guidelines and redesign the current urban primary health care system to have better coordination.